Menelaah Penilaian Kinerja Keuangan Pemerintah Daerah Melalui Laporan Realisasi Anggaran: Studi Pada Pemerintah Daerah Kota Bogor Tahun 2019-2021 - Hidayati, Nor; Gaol, Lasando Lumban; Suryani, Pesi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this study was to determine the financial performance of the Bogor City Government through analysis of the 2019-2021 budget realization report. The method applied is a descriptive quantitative approach using the level of efficiency and effectiveness as its evaluation parameters. The results of the analysis of the Bogor City Government Realization Report revealed that financial performance in the 2019-2021 range showed variations, with the average expenditure budget efficiency level reaching 89.97%. With these criteria, it can be concluded that the government has been able to manage the expenditure budget with an adequate level of efficiency, showing good ability in this regard. The level of effectiveness of the Bogor City Original Revenue (PAD) during the 2019-2021 period reached an average of 113.20%, which can be categorized as very effective. Although there was a decrease in 2020, the figure was still in the highly effective category with a percentage exceeding 100%. This indicates that the Bogor City Regional Government has been very successful in achieving the Regional Original Revenue revenue target.